Revealed comparative advantages in the services trade of the United States, the European Union and Japan: what do they tell us? - Rolf J. Langhammer (The journal of world investment & trade, 2004)
The paper argues that measuring revealed comparative advantages (RCA) in international trade in services cannot be straightforwardly compared to RCA in trade in goods. The essential difference is that services are internationally exchanged not only by cross-border trade mainly subject to relative resource endowment but also by factor movements (primarily foreign direct investment). The latter modes of supply are determined by characteristics of services such as the need of close producer-consumer proximity. In addition, the policy influence in RCA for trade in services is not dominated by border measures but by a variety of domestic regulations. The paper measures RCA for the US, EU and Japanese service trade and shows strengths on the US side and weaknesses on the Japanese side with the EU in-between. Finally, measuring RCA for US trade in two different modes (cross-border trade and commercial presence) yields similar results in some service sectors but not in all.
Keywords: F1; 330; trade in services; trade liberalization; EU customs union; Internationaler Dienstleistungsverkehr; Komparativer Kostenvorteil; Außenhandelsstruktur; USA; Japan; EU-Staaten